Kidney Involvement in Patients with Type 1 Autoimmune Pancreatitis - Vujasinovic, Miroslav (J Clin Med, 2019)
Introduction: Autoimmune pancreatitis (AIP) type 1 is a special form of chronic pancreatitis with a strong lymphocytic infiltration as the pathological hallmark and other organ involvement (OOI). IgG4-related kidney disease (IgG4-RKD) was first reported as an extrapancreatic manifestation of AIP in 2004. The aim of the present study was to determine the frequency and clinical impact of kidney lesions observed in patients with AIP type 1. Methods: We performed a single-centre retrospective study on a prospectively collected cohort of patients with a histologically proven or highly probable diagnosis of AIP according to the International Consensus Diagnostic Criteria (ICDC) classification. Results: Seventy-one patients with AIP were evaluated. AIP type 1 was diagnosed in 62 (87%) patients. Kidney involvement was present in 17 (27.4%) patients with AIP type 1: 15 (88.2%) males and 2 (11.8%) females. Laboratory and/or imaging signs of kidney involvement were presented at the time of AIP diagnosis in eight (47.1%) patients. In other patients, the onset of kidney involvement occurred between four months and eight years following diagnosis. At the time of the diagnosis of kidney involvement, eight (47.1%) patients showed elevated creatinine, and nine (52.9%) patients showed normal serum creatinine. None of the patients were treated with dialysis. Conclusions: IgG4-RKD was present in 27.4% of patients with AIP type 1, with male gender predominance. In cases of early diagnosis and cortisone treatment, the clinical course was mild in most cases. Regular laboratory control of renal function should be a part of the follow-up of patients with AIP type 1.